The magicians. Season two [videorecording (DVD)] - Ralph, Jason, 1986-; Maeve, Stella; Dudley, Olivia Taylor; Grossman, Lev (Grossman, Lev. Magician novels., 2017)
Heading into season two, this group of unlikely heroes has been thrust into even more dangerous and unfamiliar territory. They must draw upon their novice skills to defeat a threat that could destroy the magical world itself. Driven by power, revenge, and survival, they learn that those who enter the hauntingly beautiful world of Fillory will never be the same as those who leave.